Treatment self‐regulation questionnaire across three self‐care behaviours: An instrument validation study in Iranian patients with type 2 diabetes mellitus - Zahra Hazrati‐Meimaneh; Hadi Zamanian; Somayyeh Shalchi Oghli; Shima Moradnejad; Fatemeh Karkehabadi; Ata Pourabbasi; Mohammadali Amini‐Tehrani (Wiley, 2022)
Abstract Aim The study aimed at testing the validity and reliability of the Persian version of the treatment self‐regulation questionnaire (TSRQ‐15) across healthy diet, exercise and medication‐use/glucose‐monitoring among Iranian people with type‐2 diabetes. Design Cross‐sectional design. Methods Content validity was investigated by 16 experts. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were employed. Construct validity, convergent/discriminant validity and internal consistency were examined. Concurrent validity was assessed using Spearman's rho correlation across different behaviours. Results Content validity was confirmed for Persian TSRQ‐15. A three‐factor structure was revealed, in which external regulation and introjected regulations were validated, while amotivation and autonomous failed to show discriminant validity. Internal consistency was sound, and concurrent validity was approved. The Persian version of TSRQ‐15 was shown to be a valid and reliable tool for assessing motivation behind the practice of healthy diet, exercise and medication‐use/glucose‐monitoring in people with type 2 diabetes.